2016
DOI: 10.1007/s00586-016-4738-3
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the foramen transversarium in cervical vertebrae: findings, review of the literature, and clinical significance during cervical spine surgery

Abstract: Summarizing, 10 out of our 17 skeletons were presented with variations (extremely narrow or multiple foramina). This finding of hypoplastic, duplicated and triplicated foramina transversaria in unexpectedly high rates raises questions about the integrity of the contained structures, the possibility of a different path for them. These variations may induce an extra-osseous position of the vertebra artery, and the ignorance of such an event may have catastrophic consequences during a surgery in the cervical spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 18 publications
0
25
0
5
Order By: Relevance
“…Sangari SK, 2015 examined only the typical cervical vertebrae and reported the presence of double FT in 24% cases of 71 typical cervical vertebrae [10]. Zibis et al (2016) also observed doubleforamina in 14 vertebrae (13.72 %). In seven vertebrae, theduplication was bilateral (6.86 %) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Sangari SK, 2015 examined only the typical cervical vertebrae and reported the presence of double FT in 24% cases of 71 typical cervical vertebrae [10]. Zibis et al (2016) also observed doubleforamina in 14 vertebrae (13.72 %). In seven vertebrae, theduplication was bilateral (6.86 %) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Our case describes bilateral C2 congenital anomalies. The congenital variations of the cervical transverse foramina are characterized by alternate extraosseous pathways of the vertebral artery [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Comparando esse dado, estudos mostraram níveis altos de confiabilidade e reprodutibilidade das medidas por essa metodologia (CAGNIE et al, 2005;KIM et al, 2012;MOLINET GUERRA;ROBLES FUENTES;ROA, 2017;SUREKA et al, 2018;ZIBIS et al, 2018ZIBIS et al, , 2016.…”
Section: Variações Anatômicasunclassified
“…Apesar da divergência nos resultados de DU na literatura, houve concordância com relação aos níveis mais acometidos, sendo C5 e C6 os mais recorrentes para a maioria dos pesquisadores (JAÉN E., 1975;KAYA et al, 2011;METIN TELLIOGLU et al, 2018;ZIBIS et al, 2018ZIBIS et al, , 2016. Em nosso estudo, detectamos que em C6 está o nível mais acometido, com o 51% das vértebras com forame duplicado, seguido pelo nível C5, com 31%.…”
Section: Variações Anatômicasunclassified
See 1 more Smart Citation